Ação educativa nos museus do sul de Minas Gerais: uma prática direcionada aos educandos e/ ou necessária para docentes? - Sonia Maria Sanches (2016)
The reasons that leaded me to choose this object of study have their origins in the experiences I lived in my professional career, during thirty-seven years working at the Historical and Geographical Museum in Poços de Caldas ( South of the state of Minas Gerais, Brazil) as well as in teaching practice, as professor of Philosophy for eleven years. The present work refers to the educational practice in three museums in the South of the state of Minas Gerais, and aims to analyze how these places and their educational experiences contribute not only to the students learning but to the training of educators as well. Considering the experience of this researcher in her work place, and having as reference the educational practice carried out without an appropriate place for this finality, and other related museums facing a confuse scenario to receive school visits, this work looked for actual bibliographical references in this area. Data collection took place in three museums: 1) Historical and Geographical Museum in Poços de Caldas; 2) South of Minas Regional Museum; 3) National Museum of the Mangalarga Marchador Horse. The perspective of analysis was intended to reach the understanding of the moving from school to museum, and backwards from museum to school, considering the educational experience developed in those three institutions. For a better understanding of the object of study there were pointed out data related to the South of the state of Minas Gerais, and there were presented the numbers of the Professional Masters Degree. This study covered two distinct moments: 1) The data collection process at the selected places, through interviews with the museums directors; 2) A current bibliography research on the ways of utilization and appropriation of the museum by the school. There were analyzed the educational experiences related to the school people developed at the selected places, and from that analyze there was considered the creation of a Visitors Guide for the Historical and Geographical Museum of Poços de Caldas for educators.